The Effect of Storage Temperature and Time on the Concentrations of Bovine Serum Amyloid A and Its Mammary Associated Isoform - Csilla Tóthová; Oskar Nagy; Herbert Seidel; Gabriel Kováč (Veterinary Medicine International)
The objective of this study was to evaluate the effect of storage under various conditions on the concentrations of major bovine acute phase protein—serum amyloid A, and its mammary isoform. Blood samples were taken from seven clinically healthy calves, and milk samples from six clinically healthy dairy cows. The harvested blood serum and the milk samples were fractioned into aliquots. One aliquot was analyzed on the day of collection without storage. The second aliquots were stored at 4°C for 1 day, the remaining aliquots were kept frozen at −18°C for 2, 7, 14, and 21 days, and then analyzed. Blood serum was analyzed for serum amyloid A (SAA). The concentrations of mammary isoform of SAA (M-SAA) were measured in milk samples. Over time, the concentrations of SAA in serum showed a tendency of significant decrease during storage at −18°C (P<0.01). Similarly, the values of M-SAA decreased significantly in samples maintained at freezer temperatures (P<0.001). In the refrigerated samples, we found non-significantly lower values of SAA, as well as M-SAA. Presented results indicate that the storage temperature and duration may markedly affect the concentrations of bovine SAA and M-SAA.